Atmospheres and Oceans of Terrestrial Planets - Liu, Lin-gun (European Journal of Applied Sciences, 2025)
The atmospheres and oceans of the terrestrial planets are primarily made up of the two most abundant volatiles, CO2 and H2O. The possible sources and early evolutions of these volatiles during accretion are briefly elucidated. The total mass, or the gravity force/attraction force, of a planet plays the most important role to determine whether an atmosphere and/or ocean can exist on a planet. Both the Moon and Mercury are not massive enough to hold CO2, the heaviest natural volatile, to form an atmosphere. Thus, their atmospheres are virtually in vacuum (manifested by its atmospheric pressure of ~10-15 bar). Mars is not massive enough to hold H2O in its atmosphere. Therefore, Mars cannot sustain an ocean for a long period of time. On the other hand, observed geological features on Mars suggest that there were possible ancient oceans on Mars. The scenario of the origin of an ancient Martian ocean is postulated. Both Mars and Venus possess basically the same atmospheric composition with more than 95% CO2 and followed by a few percent of N2, which are consistent with the estimated critical mass (CM) for these volatiles. Earth is situated between Venus and Mars, but possesses a very different atmospheric composition. During accretion, however, there is no compelling reason that the Earth’s proto-atmosphere should be any different from those of Venus and Mars. It has been postulated that the occurrence of the Moon by a strike of a Mars-like impactor in the early stage of Earth’s life after solidification, the so-called Moon-making giant impact theory, also generated the indigenous hot soda oceans on the Earth. Further on the way of cooling, the growth of the indigenous ocean would somewhat remove CO2 from the Earth’s proto-atmosphere. The removal was later accelerated and completed when the indigenous oceans reacted with plagioclase, the most abundant mineral on the Earth, to form carbonate and clay minerals. Once CO2 was removed from the Earth’s proto-atmosphere, N2 naturally becomes the most abundant component in the Earth’s atmosphere as observed today.